Melon's Beneficial Properties And Pest Control - Guljamol Rakhmanjanovna Rakhmonova (Zien Journals, 2025)
Today, cultivation of melons and their protection against perts, diseases and alien species is a major issue in the field of crop cultivation. In particular, the fight against quarantine pest Myiopardalis pardalina Вezzihelps to reduce the melanoma production by 80–85%. It also describes the preservation of the article, and the measures it takes against it to clarify all the research findings.
Keywords: melon; melon fly; bioeology; development